Progam Pelatihan Kewirausahaan Melalui Bisnis Pembuatan Produk Kreatif Buckethand Untuk Menciptakan Masyarakat Mandiri - Andika Dwi; Eka Windha Tamaya; Imam M Yusuf; Nabila (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2023)
Community service activities are an integral part of the Tri Dharma of HigherEducation which in its implementation cannot be separated from the other twodharma, and involves all academics: lecturers, education staff, and students. Throughcommunity service, academics can be present in the midst of society.Then the 4 of us took the initiative to create a program, namely the EntrepreneurshipTraining Program Through the Buckethand Creative Product Manufacturing Businessto Create an Independent Society. With the aim of building a public image ofcreativity that is able to create an independent society.Our targets are PKK (Family Welfare Empowerment) whose address is CipaduVillage RT.006/001. This activity is held in the form of a training activity. After beinggiven the material, they were then guided to make a buckethand product whichcontained various kinds of snacks or commonly known as a snack bouquet. The endresult of this activity is that the participants in the snack bouquet training are proficientand able to create their own, develop their talents and skills in making snack bouquetsso that they can become high selling points and are able to create new innovations inentrepreneurship.Keywords: Create An Independent Society.